Localization of IEC materials of Carrascal LDRRMO through disaster management training - Arreza, Christine Marie P.
Philippines is prone to natural disasters because of its geographical location along the Pacific Ring of Fire or Typhoon belt. To prepare its people, national government makes efforts to bring down disaster management activities to local communities since they are most vulnerable by these disasters. One effort is the creation of Information, Education and Communication (IEC) materials. However, these materials tend to become too generic to address the local hazards and vulnerabilities. For most cases, the Carrascal Local Disaster Risk Reduction and Management Office (LDRRMO) use IEC materials from higher implementing agencies of RA 10121 as the conduct Disaster Management Training yearly. It is then important for the researcher to evaluate how these materials were localized by the office as they conducted the training in Brgy. Adlay last November 26-28, 2012. The researcher has evaluated the whole flow of the training, from the speaker?s delivery of IEC content down to how participant received disaster management concepts. The researcher used Laswell?s communication model to serve as the main framework for the study. Also, the study incorporated the localization to how appropriate were the IECs to the training participants, thus the Adult Learning of Malcolm Knowles. Hence all components of the Source-Message-Channel-Receiver-Effect were evaluated using William Pleiffer and John Jones? adaptation of David Kolb?s five stages of Experimental Learning Cycle (ELC). After analyzing the gathered data, the researcher found out that the localization in only on the language used by the speakers and not on the IEC contents. However, all speakers almost completed all stages of ELC. Various studies have looked at disaster management, however, only few have focused on local hazards and communities. This study will provide additional information on how IECs should be tailored to address local hazards and communities. Also, localization should be appropriate to the target audiences which are almost adults, thus the use of Pleiffer and Jones? ELC.